Metacognitive Treatment in Acquired Brain Injury and Its Applicability to Aphasia: A Systematic Review - Wadams, Amanda; Suting, Louisa; Lindsey, André; Mozeiko, Jennifer (Frontiers in Rehabilitation Sciences, 2022)
Purpose The purpose of this systematic review is to identify the utility of metacognitive therapeutic intervention for persons with acquired brain injury (ABI), with a focus on persons with aphasia. Methods A search of six databases resulted in two hundred and sixty-six unique manuscripts relating to the explicit use of metacognitive treatment for people with ABI. Two independent reviewers rated abstracts for inclusion or exclusion of the study given predetermined criteria. Twenty-nine articles, five of which included people with aphasia, were selected for inclusion in this systematic review. SCED+ and PEDro+ rating scales were used to rate the methodological quality of each study. Results Methodological quality of the 29 studies that met inclusion criteria ranged from weak to high quality studies. Three -hundred and sixty-nine individuals with ABI took part in the 29 studies. Varying treatment methods were employed. Outcome measures were inconsistent. Metacognitive treatment has been applied to people with aphasia with positive results, but efficacy of the treatment cannot yet be determined. Conclusions Metacognitive therapeutic intervention tends to be effective for persons with acquired brain injury (ABI) despite variability between intervention designs and treatment outcomes across studies. Due to so few studies with participants with aphasia, we were unable to draw conclusions regarding the efficacy of metacognitive treatment for people with aphasia. Further research on the efficacy of metacognitive treatment for this population is warranted.